Mechanical properties of ice at Norströmsgrund - Fransson, Lennart; Stenman, Ulf (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2004)
In March 2003, level ice with a thickness of 59 cm was sampled from an ice floe close to the lighthouse Norströmsgrund. Large pressure ridges were surrounding the floe, which had a diameter of about 60 meters. A total of 12 large ice cores with a diameter of 200 mm were drilled out along two rows, with an equidistance of two metres in the central part of the floe. The cores were put into plastic bags and were then directly transported with helicopter to the laboratory at Luleå University of Technology. Horizontal samples with a diameter of 70 mm were drilled from the large vertical cores at the depths 10, 20, 30, 40, 50 cm. Uniaxial compression tests on these samples were performed with three different nominal strain rates (0.5, 1, 2 x 10 -3 s-1) and three different temperatures (-1, -4, -10°C). Godkänd; 2004; 20071204 (frans)